INSTITUTIONALISATION OF RETURN MIGRATION IN LATVIA: THE CASE OF REGIONAL COORDINATORS - Prusakova, Laura; Bērziņš, Māris; Apsīte-Beriņa, Elīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Emigration countries such as Latvia institutionally should address the negative consequences of the ageing populations' economic and demographic challenges. To this aim, in 2018 network of five regional return migration coordinators was established to foster and nationally encourage return migration. The primary function of the regional coordinator is to foster and facilitate requests of potential return migrants.Drawing on interview materials collected in 2020 with return migration coordinators at the regional level – Latgale, Vidzeme, Zemgale, Kurzeme and Riga, we illustrate good-practice of return migration institutionalisation in Latvia.Our study focuses on three main fields of interest within the work of regional return coordinators: 1) what are the typical return migration paths from the coordinators' perspective? 2) what are the main challenges in coordinators' work? 3) how education-related issues for return migrants are solved?The research reveals that people typically return for family reasons and long for their homeland, traditions, and traditional settings. The research states that the main challenges coordinators' work relates to is the low standardisation level as each returnee's case is unique.